Carboxamide versus sulfonamide in peptide backbone folding: a case study with a hetero foldamer - Ramesh, Veera V. E.; Kale, Sangram S.; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic Letters, 2013)
Strikingly dissimilar hydrogen-bonding patterns have been observed for two sets of closely similar hetero foldamers containing carboxamide and sulfonamides at regular intervals. Although both foldamers maintain conformational ordering, the hydrogen-bonding pattern and backbone helical handedness differ diametrically.

Conformational modulation of peptide secondary structures using beta-aminobenzenesulfonic acid - Kale, Sangram S.; Kunjir, Shrikant M.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Chemical Communications, 2014)
This communication describes the influence of beta-aminobenzenesulfonic acid ((S)Ant) on the conformational preferences of hetero foldamers. The designed (Aib-(S)Ant-Aib)(n) and (Aib-(S)Ant-Pro)(n) oligomers display a well-defined folded conformation featuring intramolecular mixed hydrogen bonding (7/11) and intra-residual (6/5) H-bonding interactions, respectively.

Comparative study of dG affinity vs. DNA methylation modulating properties of side chain derivatives of procainamide: insight into its DNA hypomethylating effect - Gawade, Rupesh L.; Chakravarty, Debamitra K.; Debgupta, Joyashish; Sangtani, E.; Narwade, S.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Deobagkar, D. D. (RSC Advances, 2016)
Procainamide derivatives have been synthesized to investigate the role of side chains in modulating the DNA methylation level in cancer cells and gain insight into its mechanism of action. The synthesized derivatives comprised of flexible (dimethyl), constrained (pyrrolidine, piperidine, morpholine) and planar aromatic (pyridine, phenyl) side chain motifs. The affinity of procainamide and its derivatives towards the deoxyguanosine (dG) base in neutral form has been assessed by performing Differential Pulse Voltammetry (DPV) under physiological conditions. Further, molecular docking with hemimethylated CpG rich DNA acquired from an active mDNMT-1-DNA (PDB ID-4DA4) crystal structure, reveals their preferential non-covalent interaction with dG nucleobase in the intercalation cavity of the minor groove. Differential affinity of the derivatives to dG base in neutral and bound forms (DNA) is correlated with their DNA methylation modulating properties at sub-lethal concentrations. Among all the derivatives, a compound with an aromatic phenyl side chain (1) has shown a highest binding affinity for dG nucleobase in neutral form as well as for partially denatured CpG rich DNA which is attributed to the formation of p/p stacking interaction in addition to N-H/O hydrogen bonding with the pyrimidine ring of dG base. It also shows the highest cytotoxicity and global hypomethylation at a sub-lethal level in the MCF-7 cancer cell line compared to other derivatives and procainamide. A docking study has also illustrated the plausible structural basis of DNA methylation modulating a property of procainamide. Strong association of procainamide with dG bases of partially denatured CpG rich DNA via H-bonding and other non-covalent interactions may alter the active topology of DNA required by the DNA-binding regulatory proteins (e. g. DNMT-1) which is validated by a DNMT-1 inhibition assay. This systematic investigation leads to a new potent alternative to procainamide being found and gives a plausible insight into the DNA hypomethylating effect of procainamide.

Crystal engineering for intramolecular pi-pi stacking: effect of sequential substitution of f on molecular geometry in conformationally flexible sulfonamides - Shaikh, Samir R.; Gawade, Rupesh L.; Kumar, Deepak; Kotmale, Amol; Gonnade, Rajesh G.; Stuerzer, Tobias (Crystal Growth & Design, 2019)
A small library of ten sulfonamide derivatives comprising two aromatic rings was synthesized to investigate the effect of chronological positioning of the F-atom on the intramolecular pi-stacking assembly. The sequential positioning of F atoms was carried out on one of the aromatic rings that is linked to the sulfonamide moiety directly while the other aromatic ring (phenyl or pyridine) is linked by an ethyl spacer with the sulfonamide moiety. The ethyl spacer is provided to achieve the required flexibility so that both aromatic rings can bend to acquire syn conformation facilitated pi-stacking between electron-deficient and electron-rich aromatic rings. The idea was to study the interplay between hydrogen bonding and pi-stacking synthons in the conformationally flexible sulfonamide derivatives. The solid-state conformation of all the derivatives was investigated using the single-crystal X-ray diffraction technique. Crystal structure analysis revealed that the syn conformation was achieved only in trifluoro and pentafluoro sulfonamide derivatives with benzene substitution while in all other derivatives the molecules take either midway or anti conformations. None of the sulfonamide molecules with a pyridine moiety showed syn conformation. It could be because of the involvement of the pyridine N-atom in the hydrogen bonding dimeric synthon. The molecular conformation study in solution state using 2D NOESY and HOESY NMR experiments also substantiated syn conformation in a pentafluoro sulfonamide molecule with benzene substitution. The conformational analysis carried out employing density functional theory (DFT) calculations confirmed higher stability for the syn conformation over midway and anti orientations.

Crystal engineering for intramolecular π-π stacking: effect of substitution of electron-donating and electron-withdrawing groups on the molecular geometry in conformationally flexible Sulfoesters and sulfonamides - Shaikh, Samir R.; Gawade, Rupesh L.; Dabke, Niteen B.; Dash, Soumya R.; Vanka, Kumar; Gonnade, Rajesh G. (CrystEngComm, 2024)
A series of 21 sulfoester and sulfonamide derivatives comprising two aromatic rings was synthesized to investigate the effect of the presence of either electron-donating (ED) or electron-withdrawing (EW) groups on the intramolecular pi-stacking assembly. The positioning of ED or EW moieties was carried out directly on one of the aromatic rings linked to the sulfonyl or sulfonamide moieties. In contrast, the other aromatic ring (phenyl or pyridine) was connected by a -CH2-CH2- spacer with the sulfonyl or sulfonamide moiety. The purpose of having an ethyl spacer between the two aromatic rings was to achieve conformational flexibility, facilitating the intramolecular pi-stacking assembly between the two aromatic rings. The use of sulfoester/sulfonamide groups allowed more conformational flexibility to attain desired orientations in solids with the interplay of the hydrogen-bonding interactions. Between the two functional groups, sulfonamides offered a more hydrogen-rich environment due to the amine moiety and may exhibit higher H-bonding propensity than the sulfoester moiety. The central idea here was to study the interplay between the hydrogen-bonding and pi & ctdot;pi interactions. The substituent groups chosen were categorized as strong electron-withdrawing (-CF3 and -CN), weak electron-withdrawing (-Cl and -Br), neutral (-H), and good electron-donating (-CH3 and -OCH3) groups. Crystal structure analysis revealed the syn conformation for all the derivatives, enabling intramolecular pi & ctdot;pi interactions between the two aromatic rings, whereas in the sulfonamide derivatives, the molecule takes either midway or anti conformations, except for one pyridine sulfonamide derivative, which showed the syn orientation but lacked intramolecular pi-stacking interactions. The absence of any conventional H-bond forming functional groups in the sulfoester derivatives may have resulted in the syn geometry facilitated by intramolecular pi-stacking interactions. Conversely, H-bond-forming functional groups in the sulfonamide derivatives could have prevented the syn conformation. The conformational analysis carried out employing density functional theory (DFT) calculations confirmed the higher stability of the syn conformation over the midway and anti orientations. The placing of electron-withdrawing and electron-donating groups at the para position of the benzene revealed sulfoesters preferably adopts a syn geometry facilitating the intramolecular pi-stacking, but sulphonamides takes midway or anti-geometry.